Production of low-oxygen titanium powder by thermochemical and electrochemical processes: Current state and perspectives - Liguo Zhu; Lingxin Kong; Bin Yang; Baoqiang Xu (Journal of Materials Research and Technology)
Titanium (Ti) is an important structural metal material of light weight, high specific strength, corrosion resistance and excellent biocompatibility. It is a key strategic key material in the aerospace industry, and also finds broad application prospects in civil fields, such as automobile, electric powder, and biomedicine. Although Ti reserves are abundant, the extraction of Ti is very complicated and extremely challenging owing the strong affinity of Ti for oxygen. Currently, the Kroll-Hydride-Dehydride (Kroll-HDH) is the main industrial production method for the large-scale production of Ti powder. Despite decades of process optimization and development, the Kroll-HDH process still faces the problems concerning high energy consumption, heavy pollution, and high production costs. Alternative production approaches including thermochemical and electrochemical reduction, to name a few, have been proposed. This review summarizes the basic principles, characteristics, oxygen concentrations, limitations of these new methods. Several of these new processes remain in the laboratory or pilot stage and require long-term testing and evaluation before practical application. The rare earth chloride-assisted magnesiothermic reduction TiO2 method and the hydrogen assisted magnesiothermic reduction (HAMR) method can be used to prepare low-oxygen titanium powder. Both methods offer lower production costs, with significant technical advantages and are expected to find industry application in the future. The research results of this review can be used as a reference to advance the development of low-oxygen Ti preparation processes.